1998
DOI: 10.1063/1.475924
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment in nanoscale ice films: Thickness and charge trapping effects

Abstract: The yield and kinetic energy ͑KE͒ distributions of D Ϫ ions produced via dissociative electron attachment ͑DEA͒ resonances in nanoscale D 2 O ice films are collected as a function of film thickness. The 2 B 1 , 2 A 1 , and 2 B 2 DEA resonances shift to higher energies and their D Ϫ ion yields first increase and then decrease as the D 2 O films thicken. The D Ϫ KE distributions also shift to higher energy with increasing film thickness. We interpret the changes in the DEA yield and the D Ϫ KE distributions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 48 publications
5
70
0
Order By: Relevance
“…This phenomenon is akin to an attenuation length (AL) for the incident LEEs inside the film and thus limits the LEEinduced damage to a fraction of the film. Besides, most of the LEEs suffer energy loss inside the DNA molecules and end up in intermolecular traps, or via dissociative electron attachment (DEA) stabilize as atomic or molecular anions leading to film charging [50][51][52][53][54]. Both AL and film charging effects can lead to considerable error in the CS values for the formation of DNA damage if not accounted for in the data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is akin to an attenuation length (AL) for the incident LEEs inside the film and thus limits the LEEinduced damage to a fraction of the film. Besides, most of the LEEs suffer energy loss inside the DNA molecules and end up in intermolecular traps, or via dissociative electron attachment (DEA) stabilize as atomic or molecular anions leading to film charging [50][51][52][53][54]. Both AL and film charging effects can lead to considerable error in the CS values for the formation of DNA damage if not accounted for in the data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The return of secondary electrons to a positively charged surface can have significant effects in the sputtering of insulators [2]. Limited laboratory studies have focused on the charging of ice films due to charge imbalance upon ion [3] or electron [4,5] injection. Other research has examined the simpler case of charging and breakdown in rare gas solids.…”
Section: Introductionmentioning
confidence: 99%
“…The oligonucleotides were embedded into multilayer films of amorphous ice to simulate the water molecules surrounding cellular DNA. 17,18,19 The presence of water around DNA was found to modify the TNI manifold, the corresponding decay channels and thus the SSB and DSB yield functions. 20,21 More recently, theoretical studies indicated that the solvation of DNA molecules (i.e., immersion in an environment of polar molecules such as water) could significantly increase their ability to capture electrons with energies near zero or lower, via the modification of adiabatic electron affinity of solvated DNA bases in bulk water.…”
Section: Introductionmentioning
confidence: 99%